Specialization or diversification in sports development: An Integrative Review - Rojas Valverde, Daniel; Azofeifa Mora, Christian; Herrera Monge, María Fernanda Fernanda; Fallas Campos, Andrea; Herrera González, Emmanuel (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2024)
Purpose: To explore and discuss theoretical and practical scientific literature to compare sports diversification and early sports specialization as a sport and educational approach. Methods: A systematic review was conducted following PRISMA guidelines, and 61 studies were included. Results: Coaches, parents, and children consider that the best way to develop sports talent and enter the elite in sports is to practice a single discipline as early as possible to achieve specialization and maximum technical skills and physical and psychological conditions. Sports specialization paths may lead to a physical, social, and mental state that compromises their integral development. Conclusion: Sports diversification should be considered first at an early age and, afterward, the specialization once the bases of strength, conditioning, neuromuscular training, and a specific psychomotor maturation have been achieved, so that sports performance and health are not compromised in the medium or long term. It is necessary to consider that few children enter elite sports, so for many of them, sports education will be the basis for exercising their citizenship as active people.